25-OH-Vitamin D3-synthesizing ability and fatty acid composition in liver of rabbits with acute arginine pancreatitis and its correction with linseed oil - O. O. Hopanenko; Y. F. Rivis (Біологічні студії, 2013)
In this paper, we measured the level of 25-OH-vitamin D3 in blood plasma and fatty acid composition of esterified cholesterol in the liver of rabbits with acute arginine pancreatitis and its correction with linseed oil. It was found that the level of 25-OH-vitamin D3 decreased in blood plasma of rabbits with acute arginine pancreatitis. The relative amount of saturated and monounsaturated fatty acids of esterified cholesterol increased, while the content of polyunsaturated fatty acids of esterified cholesterol decreased in liver of these rabbits. Feeding with linseed oil leads to an increased level of 25-OH-vitamin D3 in blood plasma of rabbit with acute arginine pancreatitis compared with the control. Simultaneously, the fatty acid composition of esterified cholesterol was normalized in liver of the rabbits.